2009
DOI: 10.1007/s00210-009-0392-1
|View full text |Cite|
|
Sign up to set email alerts
|

Lack of specificity of antibodies directed against human beta-adrenergic receptors

Abstract: The present study was designed to investigate if antibodies against β-adrenergic receptors (βARs) can be used to determine expression of βAR in human myocardium. Western blotting was performed to investigate the specificity of antibodies directed against β 1 AR and β 2 AR in human left ventricular tissue. A comparison was made between cardiac tissue from patients with idiopathic dilated cardiomyopathy and ischemic heart disease and nonfailing donors. The antibodies directed against β 1 AR and β 2 AR recognized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 14 publications
2
38
0
Order By: Relevance
“…Specifically, it has been shown that many antibodies against β 3 -adrenoceptors (Pradidarcheep et al 2009;Cernecka et al 2012), other β-adrenoceptor subtypes (Hamdani and van der Velden 2009) or other G-protein-coupled receptors in general (Pradidarcheep et al 2008;Michel et al 2009;Adams et al 2012;Beermann et al 2012;Neumann et al 2012;Yu and Hill 2013;Cecyre et al 2014;Talmont and Mouledous 2014;Böhmer et al 2014), in many, if not most cases, lack selectivity for their cognate receptors when tested based on stringent criteria. A well-validated monoclonal antibody against β 3 -adrenoceptors (Chamberlain et al 1999) unfortunately never became available commercially and no longer is available from the original investigators.…”
mentioning
confidence: 99%
“…Specifically, it has been shown that many antibodies against β 3 -adrenoceptors (Pradidarcheep et al 2009;Cernecka et al 2012), other β-adrenoceptor subtypes (Hamdani and van der Velden 2009) or other G-protein-coupled receptors in general (Pradidarcheep et al 2008;Michel et al 2009;Adams et al 2012;Beermann et al 2012;Neumann et al 2012;Yu and Hill 2013;Cecyre et al 2014;Talmont and Mouledous 2014;Böhmer et al 2014), in many, if not most cases, lack selectivity for their cognate receptors when tested based on stringent criteria. A well-validated monoclonal antibody against β 3 -adrenoceptors (Chamberlain et al 1999) unfortunately never became available commercially and no longer is available from the original investigators.…”
mentioning
confidence: 99%
“…A greatly variable selectivity has been demonstrated for several commercially available antibodies raised against β1-, β2-, or β3-ARs (Hamdani and van der Velden 2009;Pradidarcheep et al 2009;Cernecka et al 2014b). In the present study, we tried to validate the use of the antibodies against the β-AR subtypes using KO mice and a siRNA-based approach according to recommendations on how to validate receptor antibodies ).…”
Section: Selectivity Of β-Ar Antibodiesmentioning
confidence: 97%
“…A second soft criterion used in the past is that antibodies against different subtypes of a given receptor exhibit distinct staining patters in tissues. However, studies with both knock-out mice (Everaerts et al 2009;Jensen et al 2009;Jositsch et al 2009;Lu and Bartfai 2009;Pradidarcheep et al 2008) or immunoblots comparing staining to cloned receptor subtypes (Bodei et al 2009;Hamdani and van der Velden 2009;Pradidarcheep et al 2009) demonstrate that this also is insufficient to prove selectivity. Rather we propose that at least one of the following four conditions must be met to consider an antiserum to indeed be selective.…”
Section: Criteria To Demonstrate Receptor Antibody Specificitymentioning
confidence: 99%
“…siRNA; if that leads to a major reduction of staining by a given antibody, this also constitutes reasonable evidence for its specificity. Thirdly, studies with transfection of multiple subtypes of a given receptor into the same host cell line in which the target receptor but not the related subtypes yield positive staining also can provide strong evidence for selectivity (Bodei et al 2009;Hamdani and van der Velden 2009;Pradidarcheep et al 2009). Finally, in a more classical immunological approach, it can be considered as reasonable evidence of selectivity if multiple antibodies raised against different epitopes of a GPCR, e.g.…”
Section: Criteria To Demonstrate Receptor Antibody Specificitymentioning
confidence: 99%
See 1 more Smart Citation